2015
DOI: 10.1111/febs.13555
|View full text |Cite
|
Sign up to set email alerts
|

Structures of a diverse set of colchicine binding site inhibitors in complex with tubulin provide a rationale for drug discovery

Abstract: Microtubules are dynamic assemblies of ab-tubulin heterodimers and have been recognized as highly attractive targets for cancer chemotherapy. A broad range of agents bind to tubulin and interfere with microtubule assembly. Despite having a long history of characterization, colchicine binding site inhibitors (CBSIs) have not yet reached the commercial phase as anti-cancer drugs to date. We determined the structures of tubulin complexed with a set of structurally diverse CBSIs (lexibulin, nocodazole, plinabulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
217
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(235 citation statements)
references
References 48 publications
17
217
0
1
Order By: Relevance
“…A relevant number of experimentally derived complex structures of colchicine binding site inhibitors (CBSI) were recently deposited in the Protein Data Bank (PDB) [17]. Interestingly, the superposition of the different crystal structures reveals a significant variability in the sidechains of the residues belonging to the colchicine site depending on the chemical nature of the ligand, as shown in SI_Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A relevant number of experimentally derived complex structures of colchicine binding site inhibitors (CBSI) were recently deposited in the Protein Data Bank (PDB) [17]. Interestingly, the superposition of the different crystal structures reveals a significant variability in the sidechains of the residues belonging to the colchicine site depending on the chemical nature of the ligand, as shown in SI_Fig.…”
Section: Resultsmentioning
confidence: 99%
“…

Novel quinoline derivatives carrying nitrones and oxime as nitric oxide donors were prepared and characterized using different spectroscopic techniques. Several mechanisms can explain the anticancer effect of quinoline derivatives including: topoisomerase inhibition, [21][22][23] DNA intercalation, [24] protein kinases inhibition, [25][26][27] tubulin polymerase inhibition, [28][29][30][31] and induction of apoptosis. Antiproliferative screening results showed that the 2-benzylthioquinoline nitrones 6e and 6f and the 2-methylthio analogues 6g and 6h exhibited promising antiproliferative activity especially against leukemia and colon cancer cell lines.

…”
mentioning
confidence: 99%
“…Although some anti‐tubulin agents, such as carbendazim, thiabendazole, and diethofencarb (Fig. ) and their analogs, have been used as agricultural fungicides for years, they are all classified as polymerization inhibitors, which target the colchicine site in β‐tubulin . On the contrary, the depolymerization of tubulin associated with the hydrolysis of GTP from GDP is also essential for cells .…”
Section: Introductionmentioning
confidence: 75%